A framework for assistive communications technology in cross-cultural healthcare - Forbes, David Edward (Curtin University, 2013)
Rural and remote Australian Aboriginal communities suffer seriously adverse life expectancy rates, lifestyle disease complications and hospital treatment needs due to type 2 diabetes. In great part this is due to communications barriers arising from the lack of equitable acculturation within patient-practitioner consultations. This research presents a framework foundation for a computerised patient-practitioner lingua franca. Behavioural and design science ontology development delivers an intercultural patient-practitioner type 2 diabetes assistive communications system, known as P-PAC.